Colombia a Source of Cacao Genetic Diversity As Revealed by the Population Structure Analysis of Germplasm Bank of Theobroma cacao L. - Osorio Guarín, Jaime A.; Berdugo-Cely, Jhon; Coronado, Roberto Antonio; Zapata, Patricia; Quintero, Constanza; Gallego Sánchez, Gerardo J.; Yockteng, Roxana (Frontiers Media, 2017)
Beans of the species Theobroma cacao L., also known as cacao, are the raw material to produce chocolate. Colombian cacao has been classified as a fine flavor cacao that represents the 5% of cacao world’s production. Colombian genetic resources from this species are conserved in ex situ and in-field germplasm banks, since T. cacao has recalcitrant seeds to desication and long-term storage. Currently, the collection of T. cacao of the Colombian Corporation of Agricultural Research (CORPOICA) has approximately 700 germplasm accessions. We conducted a molecular analysis of Corpoica’s cacao collection and a morphological characterization of some accessions with the goal to study its genetic diversity and population structure and, to select interesting accessions for the cacao’s breeding program. Phenotypic evaluation was performed based on 18 morphological traits and 4 biochemical traits. PCA analysis of morphological traits explained 60.6% of the total variation in seven components and 100% of the total variation of biochemical traits in four components, grouping the collection in 4 clusters for both variables. We explored 565 accessions from Corpoica’s germplasm and 252 accessions from reference populations using 96 single nucleotide polymorphism (SNP) molecular markers. Molecular patterns of cacao Corpoica’s collection were obtained amplifying specific alleles in a Fluidigm platform that used integrated circuits of fluids. Corpoica’s collection showed highest genetic diversity [Expected Heterozygosity (HE = 0.314), Observed Heterozygosity (HO = 0.353)] that is reduced when reference populations were included in the dataset (HE = 0.294, HO = 0.261). The collection was divided into four clusters based on population structure analysis. Cacao accessions from distinct groups showed some taxonomic concordance and reflected their geographic origins. For instance, accessions classified as Criollo were clearly differentiated in one group and we identified two new Colombian genetic groups. Using a number of allelic variations based on 87 SNP markers and 22 different morphological/biochemical traits, a core collection with a total of 232 accessions was selected as a primary genetic resource for cacao breeders.